47.0k views
2 votes
I need help how to solve it

I need help how to solve it-example-1
User Pridkett
by
5.1k points

1 Answer

4 votes


\tan(-x)=-\tan(x)\\\\\cos(-x)=\cos(x)\\\\\tan(x)=(\sin(x))/(\cos(x))\\\\\tan(-x)=-(\sqrt7)/(3)\to-\tan(x)=-(\sqrt7)/(3)\to\tan(x)=(\sqrt7)/(3)\\\\\sin(x):\tan(x)=\sin(x):(\sin(x))/(\cos(x))=\sin(x)\cdot(\cos(x))/(\sin(x))=\cos(x)\\\\\cos(x)=\sin(x):\tan(x)\to\cos(x)=(\sqrt7)/(4):(\sqrt7)/(3)=(\sqrt7)/(4)\cdot(3)/(\sqrt7)=(3)/(4)\\\\Answer:\ \boxed{c.\ (3)/(4)}

User Lloyd Dominic
by
4.9k points